An Index of Soviet Construction, 1927/28 to 1955 - Powell, Raymond P. (The Review of Economics and Statistics, 1959)
FOR all the interest that attaches to constant-price (physical-volume) estimates of output, it remains uncomfortably true that the outputs of some sectors are effectively unmeasurable in constant prices, at least by direct means. While this difficulty can arise from several sources, it commonly arises under either of two circumstances: where the total number of to be covered is very large, or where produced in any given year have no exact counterparts in the base year, i.e., where the products problem is unmanageably large. The conventional recourse under these circumstances is to some indirect measure of outputs, and usually to an index derived in one way or another from input data. Construction is manifestly an industry in which both of these difficulties are severe. It is a custom industry, in which single are frequently unique, and in which, even for otherwise identical products, differences in site may produce differences in costs and in services yielded. In the face of these difficulties, constant-price estimates of United States construction have been derived from input rather than output data: Simon Kuznets' estimates for decade averages, I869-I9I3, are based on materials inputs; ' his annual estimates for I 9I3-43, and the Department of Commerce annual estimates, are both essentially, though with minor qualifications, current values of outputs deflated by indexes of prices of inputs.2 The purpose of this note is to report the results of an effort to compose a constant-price index of Soviet construction.3 The substitute for a true output index employed here is the same as that used by Kuznets for the earlier period, a materials-input index. The results of the study are shown in Table i. So far as the available data and some rather incautious estimating procedures permit, this is an index of materials actually consumed in Soviet construction, not of domestic output or total consumption of construction materials conventionally defined. It is intended to include materials absorbed in gross new construction of all kinds, whether completed or in progress, no matter by whom performed or financed, and in the entire de facto territory of the U.S.S.R. as of each date. It is composed from quantity series for 59 kinds or grades of materials, some of which, however, are included for a few years only while others for some years are estimated in combination.4 It is weighted by I937 ruble prices for state industries, at wholesale. The years I92 7/28, I928/29, and I929/30 are fiscal years, beginning on October i. The war years are omitted for lack of quantity data; I94I Plan is included because of the abundance of quantity data available for that year.